Strategi Pengembangan Industri Kreatif untuk Meningkatkan Daya Saing Pelaku Ekonomi Lokal - Dias Satria (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
Creative industries are currently growing rapidly in supporting local economic competitiveness. In the course of the development of creative industries are very dependent on the 4 strategic aspects, namely: interrelated industries, supporting the institution, consumers and government policy. In this framework, the research on the state of creative industries become very urgent to be done to create economic competitiveness and strategic influence in employment. The study found that government policy in the creative industries are still not optimal in supporting the advancement of creative industries so that necessary arrangements are needed in this aspect.Keywords: Interrelated industry, supporting institution, government policy and creative industries.